Lupine allergen detecting capability and cross-reactivity of related legumes by ELISA. (1st August 2018) - Koeberl, Martina; Sharp, Michael F.; Tian, Rongkai; Buddhadasa, Saman; Clarke, Dean; Roberts, James
Highlights: Comparison of enzyme-linked immunosorbent assays for lupine allergen detection. Determination of detection capability for three different lupine species. Investigation of lupine cross-reactivity to related legumes. Abstract: Lupine belongs to the genus Lupinus and includes three species commonly consumed by humans. The Lupinus genus is closely related to other legumes, such as peanuts, soya, chickpeas, peas, lentils and beans. However, the consumption of lupine (and related legumes) can cause severe allergenic reactions. Therefore, reliable analytical detection methods are required for the analysis of food samples. In this study three commercially available ELISA test kits were analyzed for the detection capability of three common lupine species, as well as cross-reactivity to related legumes. All three ELISA test kits could detect the lupine species, though with different sensitivities. Cross-reactivity varied for the ELISA test kits and all showed some cross-reactivity to related legume samples analyzed.